Aircraft systems mechanical, electrical, and avionics subsystems integration - Moir, I. (Ian) (AIAA education series, 2001)
This text is designed to provide the reader with an introductory overview of the key system areas of commercial and military aircraft. It offers detailed illustrations and a comprehensive explanation of the concepts and principles of system design, including the evolution of system design and the functionality of the contemporary design. It also identifies emerging technological breakthroughs that may have a profound effect upon the standard for avionics technology usage and associated systems integration. The book serves as an introduction to the field of aerospace engineering for students, and provides a platform for practitioners wishing to update or extend their knowledge in light of technological advancements.